Preschool Exposure to Online Games and Internet Gaming Disorder in Adolescents: A Cohort Study - Jeong, Hyunsuk; Yim, Hyeon Woo; Lee, Seung-Yup; Lee, Hae Kook; Potenza, Marc N.; Shin, Yunmi (Frontiers in Pediatrics, 2021)
Objectives: Although considerable evidence has already been collected on the effects of early initiation of drug/alcohol consumption on addictive behaviors in adolescents, little is known about the impact of early exposure to online games during preschool ages on the risk of internet gaming disorder (IGD). We evaluated the effects of exposure to online games before entering elementary school on IGD occurrence during the secondary school years using a community-based longitudinal study. Methods: Data from 1,760 adolescents (seventh grade), who were recruited from the iCURE study and followed for two years, were analyzed. A high risk of IGD (HRIGD) was assessed by the Internet Game Use Elicited Symptom Screen, a self-reported questionnaire based on the fifth version of DSM-5 IGD criteria. Early exposure to online gaming was defined as when adolescents played online games during their preschool years. A multivariate generalized-estimating-equation model was applied to examine the independent effects of early exposure to online games on the occurrence of HRIGD during the two-year follow-up period. Results: As compared with the later-exposure group, those with early exposure to online games showed an approximately 1.7-fold greater incidence of HRIGD over the two-year follow-ups after adjusting for potential confounders including baseline IGD scores (adjusted relative risk:1.69; 95%confidence interval:1.08–2.66). Pre-specified sensitivity analyses showed that the results were robust. Conclusion: Exposure to online gaming during the preschool years increases the likelihood of occurrence of HRIGD in adolescence. Restricting exposure to online games during the preschool years should be examined as a way to reduce the risk of IGD in adolescents.